Prevalence of common mental disorders and associated factors among adults living in Harari regional state, eastern Ethiopia: a community based cross-sectional study - Abdeta, Tilahun; Birhanu, Abdi; Kibret, Haregeweyn; Alemu, Ayichew; Bayu, Kefelegn; Bogale, Kasahun; Meseret, Fentahun; Dechasa, Deribe Bekele; Wondimneh, Fenta; Abinew, Yideg; Lami, Magarsa; Wedaje, Dawud; et al. (Frontiers in Psychiatry, 2023)
Background: Common mental disorders are highly prevalent in the population, affecting people across all regions of the world. In Ethiopia, mental disorders are the leading non-communicable disorders. World Health Organization (WHO) report shows that 4,480,113 (4.7%) and 3139003 (3.3%) people in Ethiopia are estimated to suffer from depression and anxiety respectively. However, there are only limited studies conducted on common mental disorders in Africa including Ethiopia. Even if there was a previous study conducted among Harari regional state residents seven years back, nowadays there are many possible factors that could increase the prevalence of common mental disorders in the community like the novel coronavirus pandemic, ethnic war, and current socio-economic crises in Ethiopia.Objective: To assess the prevalence of common mental disorders and associated factors among adult residents of Harari regional state, eastern Ethiopia.: A community-based cross-sectional study was conducted from March 1 to March 30, 2022. A systematic random sampling technique was used to select 1192 study participants. Data were collected by interviewer-administered structured and semi-structured questionnaires. A common mental disorder was assessed by the Self-Reporting Questionnaire of 20-Item (SRQ-20) questionnaire. Data were entered into Epi Data version 3.2 and exported to Stata Version 16 for analysis. The multivariable binary logistic regression analysis with a 95% confidence interval and p < 0.05 was used to identify factors associated with common mental disorders.Result: From a total of 1192 eligible participants, 1168 responded to this survey, giving a response rate of 97.98%. The prevalence of common mental disorders among adults in the Harari Region of this study was 21.31% (95% CI,). Being female with Adjusted Odds Ratios (AOR)